The clinical role of probiotic and prebiotic supplementations in preterm infants - Giulio Perrotta (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2023)
Background: For over two decades we have been trying to study and demonstrate the role of the gut microbiota in the onset of cardiovascular, autoimmune, infectious and neurobiological diseases and more generally the clinical efficacy.  Aims: To study the clinical efficacy of the integrative use of prebiotics and probiotics in the prenatal population. Materials and methods: All clinical trials and randomized controlled trials were selected through January 6, 2023, for a useful total of 32 studies and a cohort of more than 37,000 infants, of which just under half are term infants in the control groups. Results: In the neonatal literature, studies on the clinical use of prebiotics and probiotics focus on specific topics of investigation, starting from the intestinal microbial composition and then extending the object of analysis to the effects of antibiotics on the microbiota, to the biochemical integration of these products, the use of breast milk or artificial or donor milk, the alleged claim to intervene on pathological processes arising from opportunistic infections of the respiratory tract, and also in relation to autoimmune, gastrointestinal and dermatological pathologies, up to food intolerances. Conclusions: Significant evidence emerges in the literature that supports the therapeutic use for clinical purposes of prebiotics and probiotics even in neonatology; however, most of the published studies have structural and functional criticalities that often invalidate the research design and therefore the outcome obtained and published, risking to affect negatively the significance eventually detected. Further studies are needed that can confirm and expand scientific knowledge in this particular area.